Remodeling the bladder tumor immune microenvironment by mycobacterial species with changes in their cell envelope composition - Senserrich, Jordi; Guallar-Garrido, Sandra; Gomez-Mora, Elisabet; Urrea, Victor; Clotet, Bonaventura; Julián, Esther; Cabrera, Cecilia (Frontiers in Immunology, 2022)
Intravesical BCG instillation after bladder tumor resection is the standard treatment for non-muscle invasive bladder cancer; however, it is not always effective and frequently has undesirable side effects. Therefore, new strategies that improve the clinical management of patients are urgently needed. This study aimed to comprehensively evaluate the bladder tumor immune microenvironment profile after intravesical treatment with a panel of mycobacteria with variation in their cell envelope composition and its impact on survival using an orthotopic murine model to identify more effective and safer therapeutic strategies. tumor-bearing mice were intravesically treated with a panel of BCG and M. brumae cultured under different conditions. Untreated tumor-bearing mice and healthy mice were also included as controls. After mycobacterial treatments, the infiltrating immune cell populations in the bladder were analysed by flow cytometry. We provide evidence that mycobacterial treatment triggered a strong immune infiltration into the bladder, with BCG inducing higher global absolute infiltration than M. brumae. The induced global immune microenvironment was strikingly different between the two mycobacterial species, affecting both innate and adaptive immunity. Compared with M. brumae, BCG treated mice exhibited a more robust infiltration of CD4+ and CD8+ T-cells skewed toward an effector memory phenotype, with higher frequencies of NKT cells, neutrophils/gMDSCs and monocytes, especially the inflammatory subset, and higher CD4+ TEM/CD4+ Treg and CD8+ TEM/CD4+ Treg ratios. Conversely, M. brumae treatment triggered higher proportions of total activated immune cells and activated CD4+ and CD8+ TEM cells and lower ratios of CD4+ TEM cells/CD4+ Tregs, CD8+ TEM cells/CD4+ Tregs and inflammatory/reparative monocytes. Notably, the mycobacterial cell envelope composition in M. brumae had a strong impact on the immune microenvironment, shaping the B and myeloid cell compartment and T-cell maturation profile and thus improving survival. Overall, we demonstrate that the bladder immune microenvironment induced by mycobacterial treatment is species specific and shaped by mycobacterial cell envelope composition. Therefore, the global bladder immune microenvironment can be remodelled, improving the quality of infiltrating immune cells, the balance between inflammatory and regulatory/suppressive responses and increasing survival.